Multiplier Effect Analysis Of Economic Growth Basis Sector District Gunung Mas - Melpa Hutahean; Washington Siagian (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2018)
ABSTRACTGunung Mas regency is a division of Kapuas district. Gunung Mas Regency has a relatively limited development budget, so to spur economic growth, it is necessary to know the sector or business field that became the economic base of Gunung Mas Regency. This research aims to find out: a) Economic Sector of the Field of Business which become the economic base sector of Regency Gunung Mas. b) To know the amount of multiplier (Multipplier Effect) growth of base sector on economic growth of Gunung Mas Regency. The analysis in this study was conducted in two stages. The first phase identifies the sector of the regional economic base sector and the second stage calculates the multiplier effect of the growth of the base sector on the economic growth of the Gunung Mas regency. To determine the economic base sector is used the Location Quotion (LQ) approach and to calculate the multiplier effect ) is used multiplier formula by using PDRB data of Gunung Mas Regency and PDRB and GRDP of Central Kalimantan Province. Data collection was conducted in April 2017 using the Library Study method (Library Research). These data are obtained from Gunung Mas Regency in number, Gunung Mas Gross Domestic Product issued by BPS and BAPPEDA cooperation of Gunung Mas Regency and Central Kalimantan Province GDRP. Based on the analysis, it is found that the economic structure of Gunung Mas Regency is still dominated by 2 (two) sectors, namely agriculture sector (including plantation), forestry and fishery, and mining and quarrying sector. The contribution of these two sectors to GRDP of Gunung Mas Regency reaches 45.45%.